Reimagining Integration in Counselor Educator Doctoral Training: The Complement of Convictions, Contextualized Expression, and Pedagogy - Loosemore, Paul W. (Journal of psychology and christianity, 2019)
Christian doctoral students, as the next generation of faculty, must be well-equipped to teach integration. This article provides a framework to understand Christian integration in counseling as an outworked phenomenon that is expressed from personal convictions in a specific context. Six key factors that influence the development of Christian counselors' convictions are explored, including worldview, spiritual formation, relationships, counseling theory, view of learning, and educational context. Subsequently, a substantive pedagogical response is outlined that includes practical teaching assignments to facilitate the growth of future doctoral students and master's level students.